The race to the White House 2008: Historic in many ways - Andrew Cohen (Stiftung Wissenschaft und Politik (SWP), 2008)
The first of the three acts of this long, feverish and historic presidential campaign of 2008 is over. The primary season, which stretched from the dead of winter to the end of spring, has finally produced nominees for the two major parties. Now, in the second act, the Republicans and the Democrats are mapping strategy, testing ideas and preparing to gather at their national conventions in late summer. In the third act, they will face each other in the general election this autumn. If the primaries were prologue, it will be an extraordinary contest between two unorthodox candidates unlike any before. They will spend a record amount of money, recruit new voters, and, prospectively, redraw the electoral map of the United States
Keywords: 320